2020
DOI: 10.1101/2020.09.30.321240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating Clonally Expanded T Cells Reflect Functions of Tumor Infiltrating T Cells

Abstract: Understanding the relationship between tumor and peripheral immune environments could allow longitudinal immune monitoring in cancer. Here, we examined whether T cells that share the same TCRab and are found in both tumor and blood can be interrogated to gain insight into the ongoing tumor T cell response. Paired transcriptome and TCRab repertoire of circulating and tumor-infiltrating T cells were analyzed from matched tumor and blood from patients with metastatic melanoma at the single cell level. We found th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
4
9
0
Order By: Relevance
“…Therefore, the Simpson index of the clonal repertoire measured in the periphery may be a more accurate measure of the reservoir of clonally expanding, non-terminally exhausted T cells at the time of sampling. These findings are consistent with findings in the context of extracranial melanoma 74,75 . We validated this finding orthogonally on a patient-level basis by comparing phenotypic fraction with the Morisita Overlap Index (MOI, see Methods), a measure of TCR repertoire similarity between paired samples 76 .…”
Section: Intracranial T Cells Belonging To Clonotypes Detected In Blood Show Reduced Exhaustionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the Simpson index of the clonal repertoire measured in the periphery may be a more accurate measure of the reservoir of clonally expanding, non-terminally exhausted T cells at the time of sampling. These findings are consistent with findings in the context of extracranial melanoma 74,75 . We validated this finding orthogonally on a patient-level basis by comparing phenotypic fraction with the Morisita Overlap Index (MOI, see Methods), a measure of TCR repertoire similarity between paired samples 76 .…”
Section: Intracranial T Cells Belonging To Clonotypes Detected In Blood Show Reduced Exhaustionsupporting
confidence: 92%
“…T cells, memory CD8 T cells, and IFN-responsive CD8 T cells were associated with non-clonally expanded T cells. These results are concordant with findings in both murine and clinical models of extracranial melanoma 74,75 , where there is an association between a T cell clone's phenotype and its shared presence in both the lesion and in the blood. This model of cross-talk between blood and extracranial tumors is similarly recapitulated within our cohort of melanoma brain metastases.…”
Section: While Exhausted and Cycling T Cell Clones Were Predominantly Expanded Cd4/foxp3supporting
confidence: 90%
“…Though these top four markers are negation markers (e.g., low/negative expression on TM cells), we did observe some positive markers for TM cells lower on the list, including KLRD1 and LGALS1 ( Fig. 6 D and Table S12 ), which came up in a companion study ( Lucca et al, 2021 ).…”
Section: Resultsmentioning
confidence: 59%
“…Our finding that the AUC values for the inhibitory receptors were hardly above chance for most patients suggested that this class of markers could not reliably enrich TM cells in blood. An independent study also found PDCD1 to be a poor marker for cells in patient blood with TCRs matching to those in paired melanoma samples ( Lucca et al, 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…However, recent analysis of non-melanoma skin cancer indicates the T cell response to ICB derives from a distinct repertoire of T cell clones, denoted by shared carriage of specific T cell receptors (TCRs), that migrate to the tumor upon treatment (12). In patients with MM, T cell clones are shared across tumor and blood compartments (11,(13)(14)(15)(16)(17), whereas the number of expanded clones (occupying >0.5% of the repertoire) in the periphery after the first cycle of ICB treatment associates with long-term clinical outcome (18). Thus, there is robust evidence that the peripheral clonal T cell response to ICB is clinically informative for patients with cancer and may allow for on-treatment prognostication.…”
Section: Introductionmentioning
confidence: 99%